Multikulturalisme Desa Di Bali Dalam Kontrol Negara: Implementasi Dana Desa bagi Kegiatan Lintas Budaya di Badung dan Buleleng - Piers Andreas Noak; I Ketut Putra Erawan (Universitas Islam Malang, 2019)
This study examines the implementation of village funds related to the development of cross-cultural activities in Badung and Buleleng. Whether the pattern is instructive translation of sloganitic deconcentration tasks or participatory institutionalization that sets out the need for cross-cultural issues in the village. The Tamatea Study (2006), Parker (2017), and Gottowick (2010) discuss multiculturalism as the nature of local wisdom which is described as responding to people's daily problems. Another study, Kwon (2018) and Selenica (2018) looked at multiculturalism in the perspective of intercultural conflict. This research takes a different position from previous research by criticizing the construction of state control over multiculturalism that runs at the grassroots. Control construction is seen from the management of village funds for cross-cultural activities that are operationalized through guaranteed equality of ethnic and religious groups. The research paradigm is non-positive with case studies. Data collection methods utilize observation, interviews and documentation. The perspective used is interpretive with the theory of discourse. Research results show that state control is firmly embedded in the development of multiculturalism in villages. The nature of control is meaningfully driven, administrative control of budgeting has the potential to have an inhibiting effect on the development of the potential of the village concerned, including the development of multiculturalism activities in the village. Such as overlapping regulations on financial accountability, lack of socialization of regulations and assume that village human resources have understood every multicultural development program (especially the deconcentration program), injustice attitude views the potential of the village and bias behavior rules that are biased. Various attitudes are often shown by vertical government officials, such as sub-districts, offices (OPD), and ministries, which are counterproductive to oversee the development of the attitude of the development of multiculturalism in the village. Villages are forced to translate multicultural development programs that are trapped in administrative accountability which in reality compartmentalize the potential of the resources within.